A review of process and operational system control of hybrid photovoltaic/diesel generator systems - Mohammed A.; Pasupuleti J.; Khatib T.; Elmenreich W. (Elsevier Ltd, 2023)
Meteorology; Photovoltaic cells; Renewable energy resources; Accurate estimation; Diesel generators; Hybrid photovoltaic systems; Hybrid power systems; Operational control; Performance prediction; Photovoltaic; Photovoltaic systems; Electric load dispatching